Metal-free oxidative synthesis of benzimidazole compounds by dehydrogenative coupling of diamines and alcohols. Issue 14 (17th March 2022) - Hu, Jiaming; Li, Mengjia; Wan, Jing; Sun, Jinnan; Gao, Hu; Zhang, Feng; Zhang, Zhibing
Abstract : A general catalytic protocol for the synthesis of substituted N-heterocycles by dehydrogenative coupling of diamines and alcohols. Abstract : We report a novel metal-free synthesis of benzimidazole compounds by dehydrogenative coupling of diamines and alcohols. Using NHPI as a nonmetallic catalyst combined with molecular oxygen or air as the oxidant, this transformation represents a widely applicable protocol to N-heterocycles, such as benzimidazoles, benzothiophenes, benzooxazoles and quinazolines. Flow microreactors operating under optimized conditions enabled this reaction with higher efficiency, and the total residence time was 30 min compared with the batch bubbling reactor (10 h). Moreover, a possible reaction mechanism is proposed according to the control experiments.